INCREASING THE ECONOMY OF VILLAGE COMMUNITY THROUGH BANANA WASTE MANAGEMENT - Nanning, Nanning; Abbas, Ahmad; Ibrahim, Abd Rauf; Mujahidah, Mujahidah (Universitas Negeri Medan, 2020)
The program of this community service is designed to increase the village economy through the waste recycle. This program aims to assist the community in Tanete Village of Sidenreng Rappang of South Sulawesi to increase the family economy by utilizing the banana waste. It was carried out using Participatory Action Research (PAR) approach. The sample of village community consisted of twenty people in Tanete Village of Sidenreng Rappang of South Sulawesi. The stages of its implementation were socialization, training and demonstration. The result of this program encouraged the village community successfully to make banana waste become the painting and food jam. Keywords: Banana Waste; Economy; Village.